Decision Support System for Selecting College Majors Based on Student Interests and Talents Using the SAW Method - Nainggolan, Irfan; Simangunsong, Suhendra (Bahasa Indonesia, 2025)
This article formulates and demonstrates a Decision Support System (DSS) model for selecting a college major by placing interest and talent/aptitude as the core criteria using the Simple Additive Weighting (SAW) method. The fully documented methodology includes criteria definition, normalization procedure (benefit/cost), weighting, score calculation, implementation pseudo-code, and weight sensitivity analysis. An illustrative study using a simulated dataset with five alternative study programs and six criteria shows consistent and transparent ranking for counselors and students. The results confirm the significance of interest-aptitude integration in recommendations, while demonstrating decision stability under moderate weight changes. Practical contributions include workflow design and functional specifications for web/desktop applications; further development is directed at AHP–SAW and fuzzy-SAW.